(NwYBROSNYE GAZY I IH RADIACIONNO(B-(NHIMI^ESKAQ O^ISTKA (B/s - (NbARANOWA(B, (Nr(B.(Nb(B.s; (NbUGAENKO(B, (Nl(B.(Nts; (NkOLOTYRKIN(B, (Nq(B.(Nms ((NmOSKWA (B:s (N|NERGOIZDAT(B,s, 1981)
(NzAKL(B. : (NS(B. 44s
(NsPISOK LIT(B. : (NS(B. 45s
Keywords: (NoHRANA OKRUVA@]EJ SREDYs